Probabilistic 2D Point Interpolation and Extrapolation via Data Modeling - Jakóbczak, Dariusz Jacek (Informatica, 2015)
Mathematics and computer science are interested in methods of 2D curve interpolation andextrapolation using the set of key points (knots). A proposed method of Hurwitz- Radon Matrices (MHR)is such a method. This novel method is based on the family of Hurwitz-Radon (HR) matrices whichpossess columns composed of orthogonal vectors. Two-dimensional curve is interpolated via differentfunctions as probability distribution functions: polynomial, sinus, cosine, tangent, cotangent, logarithm,exponent, arcsin, arccos, arctan, arcctg or power function, also inverse functions. It is shown how tobuild the orthogonal matrix operator and how to use it in a process of curve reconstruction.